HUBUNGAN EVA DAN MVA SEBAGAI ALAT PENGUKUR KINERJA PERUSAHAAN SERTA PENGARUHNYA TERHADAP HARGA SAHAM - R Adisetiawan; Denny Asmas (Universitas Batanghari Jambi, 2012)
The concept of Economic Value Added and Market Value Added has been getting plenty of attention in recent years as a new form of finance performance measurement. These concepts were published in 1991 by Stern Stewart & Co., a Finance Concultant in United States. Stern Stewart & Co believe that Economic Value Added is a key term to create company value and maximation of Economic Value Added. Based on this concept, research on cement company are PT. Indocement Tunggal Perkasa Tbk, PT. Holcim Indonesia Tbk, and PT. Semen Gresik Tbk, that listed at Indonesian Stock Exchange has been doing to test the pre asumption that Economic Value Added and Market Value Added has a positive correlation, and thus Economic Value Added and Market Value Added are affect the price of company’s stocks. But the result from statistical test of the research shows that Economic Value Added and Market Value Added has no correlation, and also the statistical test for the hipothesys that Economic Value Added and Market Value Added affect the stock’s price of the firm are not proven.